Penatalaksanaan Fisioterapi Pada Kasus Cerebral Palsy Spastik Quadriplegi Tipe Ekstensi Di Yayasan Sayab Ibu Yogyakarta - PURBANINGTYAS, Yunita Ayu, Umi Budi Rahayu, SPd, SSt.Ft, M.Kes (2015)
Background : spastic quadriplegia cerebral palsy is a disorder of body posture disorders that are non- progressive movement that is caused by a lesion or abnormal development of the brain that are growing or unfinished growth characterized by increased tendon reflexes, hiperkontraktilitas of all four limbs and clonus which occurs in lower limbs. modalities are given on the condition of passive exercise therapy exercise, exercise rolled, and Nebulizer. Objective : To determine the benefits of exercise therapy modalities in reducing spasticity, improve gross motor skills, as well as the benefits nebulizeruntuk reduce sputum. Methods : The method used Physiotherapy in the case that the modalities of exercise, as well as the nebulizer and evaluation by the method of measurement of spasticity with Asworth scale, gross motor ( GMFM ), and the evaluation of sputum discharge. Results : After 6 treatments showed no decrease spasticity, not good increase functional ability, and the release of sputum. Conclusion : In the case of passive exercise modality therapy and exercise training has not been able to reduce spasticity roll and improve gross motor skills and improve functional ability . But the results obtained in the form of discharge sputum with nebulizer therapy.